(untitled) (Bulletin KNOB, 2021)
The development of Amersfoort’s two city walls can be divided into five periods. The first city wall was built in the first period 1259-1379. Although Amersfoort had been granted a charter in 1259, construction of the wall did not commence until after a serious assault by troops from the duchy of Gelre (Geulders) in 1274. The defensive wall was made stronger on that side, probably in expectation of more attacks from that direction. Between 1380 and 1500 Gelre troops attacked Amersfoort on multiple occasions and offensive firepower increased. Interestingly, Amersfoort opted to build a second city wall rather than reinforcing the existing one, considerably increasing the size of the city in the process. However, the project proved difficult to finance, defend and maintain, most likely due to the stagnating economy. Instead of being demolished after the second wall was in place, the first wall was reinforced with abutting houses, thereby becoming a kind of rampart within a rampart. The new fortifications turned out to be ineffective and in 1501 the city council decided to demolish the first city wall. This freed up space for a second generation of wall houses, mostly built from reused stone and with their front elevation on the trajectory of the first wall, with the exception of the houses along Krankeledenstraat and the southern section of Breestraat. In this same period, up until 1644, there was an attempt to strengthen Amersfoort’s defences. Several fortification plans were drawn up, none of which was implemented in its entirety, most probably due to a lack of financial resources. The ramparts that were realized are concentrated in the south-west since in this period the possibility of a new Spanish incursion was greater than any threat from Gelre. In the third period, 1645-1828, the council’s approval of additional openings in the city wall marked the beginning of a gradual deterioration of the defensive works. They had always been a big budget item, yet they had not been particularly effective. Accordingly, the council decided to convert the fortifications into lucrative functions. The Davidsbolwerk, for example, was turned into a cemetery. The most extensive demolition probably started in 1778 when it was also decided to dismantle various outer and inner gates in the second city wall. By 1829 the fortifications had entirely lost their defensive function and the city council proposed converting the outer line into a green pathway encircling the city, which would have resulted in the disappearance of all remaining traces of the wall. However, this was averted in 1844 by a national ban on the demolition of fortifications and they were subsequently integrated with the walking route. City planners continued to submit applications for demolition but encountered fierce resistance from heritage organizations. In addition, many remnants avoided demolition because most urban expansion occurred outside the historical centre. This resulted in a concomitant shift in the economic focus so that the fortifications no longer needed to be sacrificed to industrial development. Towards the end of the nineteenth century, with appreciation for the heritage value of fortifications growing, money became available for their restoration and Amersfoort’s historical centre was declared a conservation area.